Effect of Glycemic Treatment and Microvascular Complications on Menopause in Women With Type 1 Diabetes in the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) Cohort - Kim, Catherine (American Diabetes Association, 2014)
OBJECTIVE: We examined the impact of intensive versus conventional diabetes treatment upon menopause among women with type 1 diabetes in the Diabetes Control and Complications Trial (DCCT), a randomized controlled trial of intensive diabetes treatment, and its observational follow-up, the Epidemiology of Diabetes Interventions and Complications (EDIC) study. RESEARCH DESIGN AND METHODS: In a secondary analysis of women in the DCCT/EDIC (n = 657), outcomes were the cumulative incidences of natural menopause and surgical menopause. Cox regression analyses were used to examine associations with treatment group, time-varying estimates of hemoglobin A(1c) (HbA(1c)), insulin dosage, BMI, and microvascular complications (retinopathy, nephropathy, and neuropathy). RESULTS: By EDIC year 18, after an average of 28 years of follow-up, 240 (38%) women had experienced natural menopause and 115 (18%) women had experienced surgical menopause. Age at natural menopause was similar in the intensive versus conventional groups (49.9 vs. 49.0 years; P = 0.28), and age at surgical menopause was similar in the intensive versus conventional groups (40.8 vs. 42.0 years; P = 0.31). In multivariable models, treatment group, HbA(1c), and microvascular complications were not associated with risk of natural or surgical menopause. Each 10 unit/day increase in insulin dosage decreased risk of natural menopause (hazard ratio [HR] 0.91, 95% CI 0.75–0.98) and each kg/m(2) increase in BMI increased risk of surgical menopause (HR 1.08, 95% CI 1.00–1.16). CONCLUSIONS: In the DCCT/EDIC, intensive versus conventional treatment group and HbA(1c) level were not associated with menopause risk. Greater insulin dose was associated with lower menopause risk.